About the sensitivity of magnetic noises to the change of the structure of the articles from cast iron KCh 30-6 surface coating - V. Ja. Kulik (Литьë и металлургия)
There is experimentally demonstrated sensitivity of the magnetic noise methods to the change of the structure of cast iron articles KCh 30-6 surface coating with an example of radiator nipple. As a result of measuring there is disclosed the increase of magnetic noise in case of presence of decarbonized lay on the surface of detail and/ or residual cementite in surface coating; at the increase of pearlite proportion in the near-surface coating there is observed the decrease of magnetic noise.